Avaliação dos parâmetros farmacocinéticos do ciprofloxacino em pacientes submetidos à cirurgia bariátrica - Lima, Mariane Cinthya Nogueira (2018)
Roux-en-Y Gastric Bypass (RYGB) is currently considered the gold standard for the treatment of obesity, chronic and multifactorial metabolic syndrome that is one of the major public health problems. RYGB, as well as obesity, can modify its pharmacokinetic behavior of drugs. The present study aimed to verify if the RYGB alter the pharmacokinetics of ciprofloxacin in patients submitted to this procedure. The clinical trial was accepted by the Research Ethics Committee of the Federal University of Ceara under CAAE no. 15509813500005054 and was characterized as an open-label, non-randomized, single dose study method with two work sessions in which participants (obese patients with bariatric surgery) received 500mg of ciprofloxacin orally. The groups were composed of 8 athletes (6 men and 6 women, mean age 38 ± 8,5 years and mean body mass (BMI) of 44.54 kg / m2 ± 5.6 kg / m2). before and after bariatric surgery. Plasma concentrations of ciprofloxacin were determined by HPLC-MS / MS and were as follows: Cmax, Tmax, ASC0-ult, Volume of distribution, half-life and Clearence. Our findings showed that RYGB didn’t alter any of parameters evaluated [Cmax (pre-surgery: 1,29 μg.ml-1.h e post-cirurgia: 1,06 μg.ml-1.h with p=0,0564), Tmax (pre-surgery: 1.68h and post-surgery: 1.63h with p = 0.8750); ASC0-ult (pre-surgery: 5.46 μg.ml-1.a post-surgery: 5.09 μg.ml-1.h with p = 0.4117), RV (preoperative: 411.97 post-surgery: 472.2L with p = 0.3539), half-life (pre-surgery: 3.46h and post-surgery: 3.96h, with = 0.8750) and Cl (preoperative: 82 , 24 L / H and post-surgery: 83.94 L / H, with p = 0.8246)], suggesting that a RYGB altered the absorption rates of Ciprofloxacin (Cmax), but not the other parameters.